Supervisors’ social dominance orientation, nation-based exchange relationships, and team-level outcomes - Sajadi, Pegah; Vandenberghe, Christian (Frontiers in Psychology, 2022)
The prevalence of teams in contemporary organizations and the trend toward diversity in a workforce composed of members from multiple countries have drawn the attention of researchers on the consequences of diversity in workplaces. While there are potential benefits to diversity, relationship conflicts among team members may also result and affect team functioning. The aim of the present study was to explore how supervisors’ social dominance orientation, a tendency to support the arbitrary dominance of specific social groups over others, may relate to relationship conflicts and reduced team commitment within teams. A two-wave study in a sample of 931 individuals from 108 workgroups was conducted to examine the relationship between supervisors’ social dominance orientation and team functioning. Analyses indicated that supervisor social dominance orientation was associated with increased within-team differentiation of leader-member exchange (LMX) relationships based on team members’ national origin. Such LMX differentiation (LMXD) was related to more within-team relationship conflict and in turn to reduced collective team commitment. The implications of these findings for research on supervisor social dominance orientation, within-team nationality diversity, and team functioning are discussed.